2021
DOI: 10.3390/rs13163254
|View full text |Cite
|
Sign up to set email alerts
|

Morphometry and Debris-Flow Susceptibility Map in Mountain Drainage Basins of the Vallo di Diano, Southern Italy

Abstract: In watershed mountain basins, affected in the last decades by strong rainfall events, the role of debris-flow and debris flood processes was investigated. Morphometric parameters have proven to be useful first-approximation indicators in discriminating those processes, especially in large areas of investigation. Computation of morphometric parameters in 19 watershed mountain basins of the western side valley of the Vallo di Diano intermontane basin (southern Italy) was carried out. This procedure was integrate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 51 publications
0
5
0
Order By: Relevance
“…Flow-R, a distributed empirical model, was implemented with great success not only in this study but also in many studies in the literature. Giano et al [2], Polat and Erik [60], Charbel and El Hage Hassan [50], and Jiang et al [51] discussed whether Flow-R and observed landslide runout results are compatible. The researchers concluded that Flow-R results are well matched with the observed results.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Flow-R, a distributed empirical model, was implemented with great success not only in this study but also in many studies in the literature. Giano et al [2], Polat and Erik [60], Charbel and El Hage Hassan [50], and Jiang et al [51] discussed whether Flow-R and observed landslide runout results are compatible. The researchers concluded that Flow-R results are well matched with the observed results.…”
Section: Discussionmentioning
confidence: 99%
“…Applying a machine learning algorithm was advantageous in this study during the preparation of a susceptibility map to obtain quite reliable shallow landslide initiations. Flow-R software can also be implemented to distinguish landslide initiations by applying a grid-based overlay approach [2,50,51,54]. However, the pre-determination of landslide initiations via machine learning is thought to have a positive effect, increasing the success of the analyses with respect to the accuracy of the runout distance probability.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The development and distribution of geological disasters are closely related to geological and environmental conditions, topography and geomorphology, meteorology and hydrology, vegetation conditions, and human engineering activities (Giano et al 2021). Debris-flow is a kind of sudden geological disaster, with the characteristics of fast movement and short duration (Liu et al 2019).…”
Section: Introductionmentioning
confidence: 99%